Efecto simbiótico a base de Sacchromyces cerevisiae y bacillus subtilis sobre parámetros zootécnicos en pollos COBB500 - Gutiérrez Murillo, Silvia Magdalena (2017)
ABSTRACT The symbiotic effect based on Saccharomyces cerevisiae and Bacillus subtilis on zootechnical parameters in 300 Cobb 500 chicks distributed in two treatments: group control (balanced without application of symbiotic) and the experimental group (balanced with application of symbiotic), data were evaluated using the comparison of means using Student's T test for non-paired samples; a highly significant difference was found (p<0.01) in the final weight, being the highest average of 2645, 4g for the control group, there is no significant difference (p<0.05) for the other variables, reporting that the experimental group presented the best averages 200,1g/d final food consumption and feed conversion to the sixth week of 1.92, in the experimental group reported average higher for performance to the canal and abdominal fat with values of 74.2% and 37,3g in your order. Other variables as adjusted feed conversion, he obtained a value of 0.15 USD and the production index earned a good rating with 318.96, both for the control group, the experimental group reported that there was no mortality and immunologic variables found no significant difference (p<0.05), it evidence that the higher weights of spleen, thymus and concentration of red blood cells correspond to the control group 2,2g 0,6g and 28.3 x106mc/µl respectively, in the experimental group noted that Bursa Fabricii obtained the greatest middle weight with 2,3g. It is concluded that the use of symbiotic is ideal for maintaining immunological parameters in appropriate values.